Paradigma Ekoteosentris dalam Penanggulangan Sampah Darat Perspektif Hukum Islam - Nurhildawati N; Andi Huzaifa; Azman Arsyad; Lomba Sultan (Media Hukum Indonesia (MHI), 2026)
This study aims to analyze the problem of land waste in Indonesia, examine the essence of the ecotheocentric paradigm as an environmental ethic, and explain its implications for waste management from the perspective of Islamic law. This research employed a qualitative library research approach using the Qur'an, Hadith, books, scientific articles, legislation, and other relevant literature as data sources. The data were analyzed using a descriptive-analytical method. The findings reveal that Indonesia's waste problem is caused not only by increasing waste generation, inadequate infrastructure, and weak regulatory implementation but also by an anthropocentric paradigm that encourages environmental exploitation. The ecotheocentric paradigm offers a comprehensive ethical framework by integrating the relationship between God, humans, and nature, positioning environmental preservation as both a religious mandate and an ecological responsibility. From the perspective of Islamic law, this paradigm reinforces the principles of khalifah, amanah, m?z?n, and maq??id al-shar?'ah through the promotion of public benefit and the prevention of environmental harm. Therefore, effective waste management requires not only technical measures but also the transformation of moral and spiritual awareness to achieve sustainable environmental stewardship.